Adsorption of Cd(II), Cu(II) and Ni(II) ions by cross-linking chitosan/rectorite nano-hybrid composite microspheres. (5th October 2015) - Zeng, Lixuan; Chen, Yufei; Zhang, Qiuyun; Guo, Xingmei; Peng, Yanni; Xiao, Huijuan; Chen, Xiaocheng; Luo, Jiwen
Highlights: The cross-linking chitosan/rectorite nano-hybrid composite resins were prepared. The adsorption of the resins was investigated in single and binary metal systems. The adsorption capacity of the resins followed the order of Cu(II) > Cd(II) > Ni(II). EDTA desorbed metals from resins better than HCl. Coordination bonds were formed between metals and the nitrogen atoms of resins. Abstract: Chitosan/rectorie (CTS/REC) nano-hybrid composite microsphere was prepared by changing the proportion of CTS/REC with 2:1, 3:1 and 4:1. Compared with the pure cross-linking chitosan microsphere, the nano-hybrid composite microsphere was proved to have better sorption capacity of Cd(II), Cu(II) and Ni(II), especially 2:1(CTS/REC-1). The adsorption behavior of the microsphere of Cd(II), Cu(II) and Ni(II) was investigated in single and binary metal systems. In single system, the equilibrium studies showed that the adsorption of Cd(II), Cu(II) and Ni(II) followed the Langmuir model and the pseudo-second-order kinetic model. The negative values of (Δ G ) suggested that the adsorption process was spontaneous. In binary system, the combined action of the metals was found to be antagonistic and the metal sorption followed the order of Cu(II) > Cd(II) > Ni(II). The regeneration studies indicated that EDTA desorbed Cd(II), Cu(II) and Ni(II) from cross-linking microspheres better than HCl. The FT-IR and XPS spectra showed that coordination bonds were formed between Cd(II), Cu(II) and Ni(II) and the nitrogen atoms of cross-linking CTS/REC nano-hybrid composite microspheres.